Litio en Psiquiatría. / Lithium in Psychiatry. - Baldessarini, Ross J. (2014)
Background: Lithium is a light, metallic element and minerals containing it are most abundant in the Andes. John Cade introduced lithium carbonate for the treatment of mania in 1949, opening the era of modern clinical psychopharmacology. Lithium remains the most extensively studied mood-stabilizing agent. It has had a revolutionary impact in supporting bipolar manic-depressive disorder as a discrete diagnosis, and on psychiatric therapeutics. Methods: We survey the development of lithium treatment in psychiatry, including findings concerning effects on suicide. Results: Lithium is the most extensively studied treatment for bipolar disorder and the prototypical mood-stabilizing agent, despite emergence of anticonvulsants and modern antipsychotics. In addition to limiting recurrences of mania, and some reduction of recurrences of bipolar depression, lithium has demonstrated protective effects against suicide. All treatments for bipolar disorder have notable limitations, including sometimes serious adverse effects, incomplete prevention of recurrences of mania and limited prevention of depression, which accounts for three-quarters of the approximately 50% time-ill in long-term follow-up with standard treatments. Lithium can be toxic in untreated overdoses; safe dosing requires monitoring of serum concentrations. Lithium also may have mild teratogenic effects, but far less than those of anticonvulsants used for bipolar disorder. Conclusions: Lithium opened the era of modern psychopharmacology and continues as the best-established mood-stabilizing treatment for bipolar disorder as well as having strong evidence of suicide-preventing effects.